Reconstruction using low-porosity β-tricalcium phosphate for a chondroblastoma in the proximal humeral epiphysis. Issue 12 (5th December 2022) - Sakamoto, Akio; Noguchi, Takashi; Matsuda, Shuichi
Abstract: Chondroblastoma is a locally aggressive tumor, commonly occurring in the epiphysis of long bones. Damage after curettage at the joint surface can occur. Low porosity β-tricalcium phosphate (β-TCP) blocks are characterized by their high compression resistance. Reconstruction in which low-porosity β-TCP blocks are used as a strut have been reported for bone tumors around the knee. In the current report, a 13-year-old female with a chondroblastoma that extended to the subchondral bone of the proximal humeral epiphysis was treated with curettage and strut reconstruction using low-porosity β-TCP blocks. The implanted β-TCP blocks were incorporated without damage or shoulder dysfunction. Application of the strut reconstruction method using low-porosity β-TCP blocks is suitable for a chondroblastoma of the epiphysis in the humerus.